Law and Political Expertise in Plato’s Statesman (Revista Archai, 2025)
Remarks made by the Eleatic Visitor at Statesman 293a-300e are often read as implying that laws are hopelessly defective in comparison with expert political knowledge. Specifically, laws seem inadequate to the task of capturing the variability, mutability, and finely-grained detail of human life (294a6-b7). On the other hand, the Visitor endorses a strict form of law-abidingness for non-ideal constitutions. The tension between these positions has greatly exercised scholars. In this paper, I argue for a reading on which (1) the political expert, no less than laws, must rely on “rougher methods,” i.e. generalizations across individual cases; (2) law-making is a constitutive part of the statesman’s expertise; (3) laws are necessary for political communities and their value exceeds the merely instrumental or heuristic.